Determining Factors of Indonesian Coffee Demand in the US Market: Using LA/AIDS Approach - Fitri, Febti Aulia; Syafrial, Syafrial; Toiba, Hery (Universitas Panji Sakti, 2024)
Indonesia has long been the largest coffee producer and exporter in the world. However, competing Asian countries, namely Vietnam and India, dominate the world coffee trade as ranked fourth and sixth. To face increasingly competitive market conditions, it is necessary to look at the determinants of demand for Indonesian coffee and its competition. This research provides an update using the LA/AIDS (Linear Approximate Almost Demand System) model approach to explore the factors that influence demand for coffee from Indonesia, Vietnam, and India, focusing on price elasticity and coffee expenditure elasticity in the US market. The data is time series data from 1992-2021 and the US market as the destination country. The results show that the factors influencing demand for Indonesian coffee in the US are expenditure, Indian coffee prices, GDP per capita, population, unemployment rate, and CPI. Coffee from Indonesia is sensitive to US spending changes (1,010%) and elastic. The price elasticity value for Indonesian coffee has a negative sign. The cross-price elasticity value of Indonesian coffee compared to Vietnamese coffee is complementary, whereas Vietnamese coffee to Indonesian coffee is a substitute. Meanwhile, Indonesian coffee is complementary to Indian coffee and vice versa.